Positioning Knowledge Management As Key Success Factor In The Growth Of Cooperatives In Malaysia - Bidin, Yeop Hussin (Asian Academy of Management (AAM), 2007)
Economic and business challenges in the new millennium have shaped the manner cooperative movement in Malaysia charts its future outlook. After almost 82 years, a national policy was launched by the Government on January 2004 to assist in the comprehensive development of the cooperative movement. The National Cooperative Policy (NCP) will ensure that the huge resources of the cooperatives can be harnessed to generate and contribute to the economic growth of the country. However, in the light of many issues such as weak structure and the absence of good corporate governance in some cooperatives, the present Cooperative Act 1993 is being reviewed and several new provisions would be added to increase supervision, monitoring and enforcement against existing cooperatives in Malaysia. It is quite imperative that by regulating the operation of cooperatives will require also the managing of intellectual and human capital assets that exist in the movement. Through establishing a framework and terms of reference such that fundamental elements of knowledge management can be instilled are prerequisites to developing innovativeness in this growing economic sector. The sharing of knowledge among the cooperatives will eventually produce better and more educated human resources that are able to experience greater control over the works and the administration of their quality working life. Structural analysis of the cooperative movement indicates the significant influence of knowledge management in sustaining its future growth given the timely introduction of the NCP. Thus, measures taken to underline this influence will also be addressed to represent the cooperative movement's readiness to face economic and business challenges in Malaysia.